Haudenosaunee Indigenous Knowledge as Reflected in Oren Lyonâ€™s â€œWhere is the eagle seat?â€, an Oration to United Nations - Pukan, Elisabeth Oseanita (Universitas Sanata Dharma, 2016)
Various problems that people in the world face today, such as environmental and political problems and not to mention human rights issue, cannot all be answered with modern knowledge and technology. In fact, many of these problems are caused by the excess use of technology and some modern values which are not sustainable and not egalitarian. The study about Indigenous knowledge, therefore, is important to be conducted that people may have alternative ways to address world problems. This study attempted to discover the Indigenous knowledge of Haudenosaunee, one of Native American Nations in United States, which is reflected in Oren Lyonsâ€™ oration entitled â€œWhere is the Eagle Seat?â€. Anthropological approach is used in this research. Ethnographical data of the Haudenosaunee are utilized to trace the Indigenous knowledge in the oration text. In interpreting the text, the researcher used Paul Ricoeurâ€™s interpretation theory from the hermeneutic tradition. This study found six Haudenosaunee Indigenous Knowledge, i.e. justice and equality among people, equality between people and the natural world, earth as a mother and American Continent as Turtle Island, sustainability and concern for future generation, the power of the Creator and the natural law, and unity,. All of these Indigenous values are used by Lyons to address world problems and the problems that Native American people face since the coming of European settlers in their land. Keywords: Haudenosaunee, indigenous knowledge, Chief, faithkeeper